Proiectarea încălţămintei - Mihai, Aura, 1968- (Performantica, 2009)
"The Footwear Pattern Making manual addresses to students and teachers from universities and vocational schools, as well as to designers and pattern makers from footwear companies and it uses a combination between two classical methods: the 3D footwear modelling on a special form namely the last and the method of graphical construction of the 2D patterns based on the mean form and the 2D standard grid. This approach requires for 3D design to be created first directly on the last and then accurately transferred into a 2D standard design, and finally being transformed into working patterns. The book gives answers to specific problems regarding footwear design and pattern making by using the theoretical and scientific concepts for footwear construction based on the link among three elements: foot, last and footwear. The basis of footwear pattern making is given within the following chapters: Basic Stages in Producing Footwear Patterns From 3D Design, Producing Standard Forme of the Last, Producing Design Standard (Master Pattern), Pattern Making for Women’s Court Shoe, Pattern Making for Men’s Casual Shoe (Oxford, Derby), Pattern Making for Children’s Shoe, Pattern Making for Loafers, Pattern Making for Trainer/ Sport Shoe, Pattern Making for Women’s Sandals, Pattern Making for Children’s Boots, Pattern Making for Women High Boots, Producing Lining Patterns, Elements for Designing Bottom Components."--Anotace od dodavatele
Keywords: obuvnické modelářství; obuv; shoe modeling; footwear; příručky; handbooks, manuals, etc